Introduction to sunspots and lotteries. - Prescott, Edward C.; Shell, Karl (Journal of Economic Theory, 2002)
This introduces the symposium on sunspots and lotteries. Two stochastic general-equilibrium concepts, sunspot equilibrium (SE) and lottery equilibrium (LE), are compared. It is shown that, for some general, pure-exchange economies which allow for consumption nonconvexities or moral hazards, the set of LE allocations is equivalent to the set of SE allocations provided that the randomizing device can generate events of any probability. Journal of Economic Literature Classification Numbers: D51, D82, D84, E32. |Sc 2002 Elsevier Science (USA)